Network Governance-Based Strategy in Increasing The Capacity of The Fostered Child Development Program at The Special Child Development Institution for Grade II Jakarta - Gebrena, Muhammad Rafli; Adinda Puspita Ningrum; Arnazaye, Furaihan Kamyl; Lina Miftahul Jannah (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2024)
This research examines the implementation of network governance in the coaching program at the Jakarta Class II Special Children's Development Institution (LPKA). Using social network analysis techniques and single case studies, this research aims to construct a network management strategy between actors in the implementation of the LPKA Class II Jakarta coaching program. Data were collected through analysis of the institution's website, observations, and interviews. This research found that there were differences in interaction density in network structure and program effectiveness before and after the transfer of LPKA from Salemba to Cinere in 2020. The analysis of social networks in this research found three main characteristics of interaction in that period: information sharing, social action, and procurement of goods and services. The implementation of programs, projects, and policies that occur within these three characteristics can bring good network management if it pays attention to four aspects, namely orientation to children's needs, a clear technical framework, the involvement of actors at various levels, and continuous evaluation. This research concludes that institutional network management can increase the capacity of implementing coaching programs at LPKA in a sustainable manner through re-identification of child development programs/projects/policies, the creation of a technical framework for the program, the identification of actors at various levels, and the establishment of a continuous evaluation scheme for coaching programs at LPKA